GAMBARAN BUDAYA ORGANISASI PADA PT CAB - Octavian, Ivan; Omega, Petrayuna Dian (Noetic Psychology, 2011)
The massive competitions in bussiness era make organizations need to get more active to face the competitions atmosphere. PT CAB is one of the company in Jakarta that has core bussiness in clothing production and distribution. This company has been growing and want to start to go public in several years later. That purpose can be reached if organization has and know organization culture that suitable with company vision, because organization culture has a big role to reach the company vision. To know dominant type of organization culture in PT CAB, then it needed to observe using a tool Organization Culture Assessment Instrument (OCAI). Observation result showed that organization culture in PT CAB nowadays is clan culture, a culture with high tolerance characteristic, but situation that needed to exist sustainability is market culture, where as the main focus is reach the organization target.ÃÂ Keywords: Organizational culture, Organizational Culture Assessment Instrument (OCAI), Clan, Adhorarchy, Market, Hierarchy